2010
DOI: 10.2172/1023207
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Review of Filtration Studies for Waste Treatment at the Hanford Site

Abstract: SummaryThis document completes the requirements of Milestone 1-2, PNNL Draft Literature Review, discussed in the scope of work outlined in the EM-31 Support Project task plan WP-2.3.6-2010-1. The focus of task WP-2.3.6 is to improve the U.S. Department of Energy's (DOE's) understanding of filtration operations for high-level waste (HLW) to enhance filtration and cleaning efficiencies, thereby increasing process throughput and reducing the sodium demand (through acid neutralization). Developing the processes fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 86 publications
0
14
0
Order By: Relevance
“…The results of this literature review are reported in Daniel et al (2010b). The main objective of this report was to identify research areas that would allow improvement of current PNNL models for filtration of HLW (like that proposed in Daniel et al 2010a). To improve the predictive value of PNNL models, the literature review report recommended two areas of additional research:…”
Section: Need For Additional Fouling and Chemical Cleaning Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of this literature review are reported in Daniel et al (2010b). The main objective of this report was to identify research areas that would allow improvement of current PNNL models for filtration of HLW (like that proposed in Daniel et al 2010a). To improve the predictive value of PNNL models, the literature review report recommended two areas of additional research:…”
Section: Need For Additional Fouling and Chemical Cleaning Studiesmentioning
confidence: 99%
“…Issues of long-term filter dynamics and solution chemistry impacts are discussed extensively in the literature review (Daniel et al 2010a), and as such, readers are referred to that document, and an in-depth discussion of these topics is not provided herein. In contrast, the literature does not extensively discuss chemical cleaning approaches in detail.…”
Section: Need For Additional Fouling and Chemical Cleaning Studiesmentioning
confidence: 99%
See 3 more Smart Citations